High-nickel polycrystalline ternary positive electrode material and preparation method thereof
By mixing the precursor, lithium hydroxide monohydrate and M-containing compounds and sintering at high temperature, the high-nickel ternary cathode material has been solved, and high specific capacity, long cycle performance and thermal stability are achieved, while reducing production costs.
Patent Information
- Application Number
- CN202411799701.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-18
AI Technical Summary
The existing high-nickel ternary cathode materials have high production costs, and their specific capacity is not high enough, their circulation performance is poor, and their thermal stability is poor.
By mixing the precursor, lithium hydroxide monohydrate and M-containing compound and sintering at high temperature, the dual modification of the high-nickel polycrystalline ternary cathode material is achieved, which avoids secondary sintering in the process and reduces production costs.
The high specific capacity, long cycle performance and thermal stability of high nickel ternary cathode materials are achieved, while reducing the preparation cost.
Smart Images

Figure CN119637956A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a high-nickel polycrystalline ternary positive electrode material and a preparation method thereof. Background Art
[0002] Nowadays, the application range of lithium-ion batteries is expanding from portable devices to electric vehicles (EVs), playing a vital role in daily life. With the wider application range of energy conversion and storage, the demand for high energy density lithium-ion batteries (LIBs) is growing rapidly. The energy density and cost of LIBs largely depend on their cathodes, so the industry has been focusing on developing high energy density cathode materials. High nickel ternary layered materials are currently widely used as high energy density lithium-ion battery cathode materials. High capacity can be provided by increasing the nickel content in the layered cathode materials, but when the nickel content is greater than 80%, the synthesis process becomes more complicated and a pure oxygen environment needs to be maintained during the reaction. At the same time, the prepared high nickel ternary cathode materials also face many challenges in their application: (1) Ni generated in the delithiation state 4+ Side reactions occur with the electrolyte, which will consume the electrode active materials and the electrolyte. The high residual lithium (lithium hydroxide and lithium carbonate) on the surface of the high nickel material will also react with the electrolyte; (2) Li / Ni cation mixing always occurs in the high nickel layer oxide because Li + (0.076nm) and Ni 2+ The similar ionic radius of (0.069 nm) will inhibit lithium diffusion and increase reaction impedance, resulting in irreversible capacity loss; (3) The mechanical strain caused by anisotropy will lead to the nucleation and propagation of microcracks, allowing electrolyte to penetrate into them and accelerate structural degradation.
[0003] The commonly used modification strategies in the industry are to modify the surface through coating and replace some of the bulk elements through bulk doping. 4+The side reaction between the electrolyte helps to reduce phase change, improve structural stability, and inhibit the dissolution of transition metal (TM) ions. Doping can reduce the structural instability of the electrode by hindering the movement of TM and oxygen loss. The coating mainly provides surface protection from external materials, while doping changes the internal structure of the material. The use of two modification strategies alone cannot effectively improve the energy density and cycle stability of the positive electrode material. The prior art mostly uses a method of doping by one sintering and a method of coating by two sintering. Combining the advantages of the two modification methods, the electrochemical properties of high-nickel ternary positive electrode materials are further improved. For example, a nickel cobalt manganese oxide lithium positive electrode material and a preparation method thereof disclosed in Chinese patent CN109686938B introduces doping elements and combines two-stage sintering to obtain a magnesium ion-doped gradient nickel cobalt manganese oxide lithium positive electrode material. However, this technology not only increases the preparation cost, but also cannot effectively improve the performance of the ternary positive electrode material. Therefore, the industry is in urgent need of a method that can achieve dual modification of high-nickel ternary positive electrode materials by doping and coating on the basis of cost savings, which plays an important role in reducing surface residual lithium, inhibiting side reactions, controlling the generation of microcracks, and stabilizing the crystal structure, so that the prepared high-nickel ternary positive electrode materials have high specific capacity, long cycle performance and thermal stability. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the preparation cost of the existing high-nickel ternary positive electrode material is high, and the obtained high-nickel ternary positive electrode material has an insufficient specific capacity, poor cycle performance and poor thermal stability; the purpose is to provide a high-nickel polycrystalline ternary positive electrode material and a preparation method thereof, which solves the problem of high preparation cost, and the problem that the obtained high-nickel ternary positive electrode material has an insufficient specific capacity, poor cycle performance and poor thermal stability.
[0005] The present invention is achieved through the following technical solutions:
[0006] The present invention provides a method for preparing a high-nickel polycrystalline ternary positive electrode material, comprising the following steps:
[0007] The precursor, lithium hydroxide monohydrate and the M-containing compound are mixed, sintered at high temperature, kept warm and then cooled to obtain a high-nickel polycrystalline ternary positive electrode material.
[0008] Wherein, the M-containing compound includes a multivalent ionic compound whose maximum valence state is positive trivalent.
[0009] As a possible design, the weight ratio of the above-mentioned precursor and lithium hydroxide monohydrate is 2-2.5:1, and the added amount of the M-containing compound is 0.5-2wt% of the mixture of the precursor and lithium hydroxide monohydrate.
[0010] As a possible design, the precursor, lithium hydroxide monohydrate and the M-containing compound are mixed by dry mixing.
[0011] As a possible design, M in the above-mentioned M-containing compound includes at least one of Na, K, Mg, B, Al and Yb.
[0012] As a possible design, the above-mentioned M-containing compound includes Yb 2 O 3 , YbF 3 、Yb(OH) 3 and / or Yb 2 (CO3) 3 .
[0013] As a possible design, the above-mentioned precursor is a nickel-cobalt-manganese hydroxide precursor.
[0014] As a possible design, the nickel-cobalt-manganese hydroxide precursor is prepared by the following method:
[0015] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution;
[0016] The salt solution, the precipitant solution and the complexing agent are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
[0017] As a possible design, the above-mentioned high temperature sintering is carried out at 700-750°C for 10-20 hours, and after cooling, a ternary positive electrode material is obtained.
[0018] The present invention also provides a high-nickel polycrystalline ternary positive electrode material prepared by the above method, wherein the chemical formula of the high-nickel polycrystalline ternary positive electrode material is Li n Ni (1-a-b) Co a Mn b M c O 2 .
[0019] As a possible design, the above chemical formula Li n Ni (1-a-b) Co a Mn b M c O 2 , 1.00≤n≤1.09, 0.00<a<0.20, 0.01≤b≤0.10, 0.005≤c.
[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0021] The present invention uses an M-containing compound, which contains a large dose of low-valent multi-element ion compounds, which are evenly distributed through dry mixing. Since the M-containing compound elements enter the positive electrode material through solid phase diffusion, the diffusion speed is slow. Because the dosage used is relatively large, during the sintering process, when part of it enters the interior of the positive electrode material, part of it still exists on the surface, thereby achieving double modification of the high-nickel ternary positive electrode material in the subsequent high-temperature sintering, avoiding secondary sintering in the process, and achieving cost control in the production process. At the same time, the entry of low-valent ions into the bulk phase doping can stabilize the material crystal structure, and the low-valent ions can inhibit Ni in the charging stage. 4+ The generation of Ni 4+ Side reactions occur with the electrolyte, reducing the consumption of electrode active materials and electrolytes, and improving the material's cycle performance. In addition, low-valent multi-element ions can coat the secondary particles of the material more evenly, and can react with the residual alkali on the surface of the high-nickel positive electrode to generate lithium-containing compound fast ion conductors to accelerate the transmission of lithium ions during charging and discharging, improve the material capacity and rate performance, and can effectively avoid direct side reactions between active materials and electrolytes through coating, effectively improving the cycle life of ternary positive electrode materials. In addition, since M-containing compounds are ionic compounds with low melting points, they are easier to enter the interior of ternary positive electrode materials during the sintering process, and during the entire sintering process, part of the M-containing compound enters the bulk phase and then enters the crystal, part exists between the grains, and part remains on the surface of the material. The M-containing compound existing between the lattices can inhibit the growth of primary particles, and will generate lithium-containing compound fast ion conductors between the primary particles with lithium salts, forming a mutually continuous fast ion conductor network between the primary particles, and coating on the surface of the primary particles, improving the material capacity and rate performance.
[0022] The invention dopes the M-containing compound with the precursor, lithium hydroxide monohydrate and the M-containing compound by dry mixing, thereby avoiding the generation of wastewater containing doping elements and reducing the cost of wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0024] Figure 1 This is a SEM image of the material obtained in Example 4 of the present invention;
[0025] Figure 2 This is the SEM image of the material obtained in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0026] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0027] In one aspect, the present invention provides a method for preparing a high-nickel polycrystalline ternary positive electrode material, comprising the following steps:
[0028] The precursor, lithium hydroxide monohydrate and the M-containing compound are mixed, sintered at high temperature, kept warm and then cooled to obtain a high-nickel polycrystalline ternary positive electrode material.
[0029] Wherein, the M-containing compound includes a multivalent ionic compound whose maximum valence state is positive trivalent.
[0030] By selecting precursors, lithium hydroxide monohydrate, M-containing compounds and M-containing compounds for mixing and sintering, the production cost can be controlled, and during the sintering process, the low-valent ions in the M-containing compound are prompted to enter the lattice, inhibiting the growth of primary particles, avoiding strength reduction, and improving the thermal stability of the material; they will react with lithium salts to generate lithium-containing compound fast ion conductors between primary particles, forming a mutually continuous fast ion conductor network between primary particles and coating the surface of primary particles, thereby improving the material capacity and rate performance; low-valent ions can inhibit Ni from charging during the charging stage. 4+ The generation of Ni 4+ It can react with the electrolyte to produce side reactions, reduce the consumption of electrode active materials and electrolyte, and improve the material's cycle performance. It can also coat the secondary particles of the material more evenly, and can react with the residual alkali on the surface of the high-nickel positive electrode to generate lithium-containing compound fast ion conductors to accelerate the transmission of lithium ions during charging and discharging, improve the material's capacity and rate performance, and can effectively avoid direct side reactions between active materials and electrolytes through coating, effectively improving the cycle life of ternary positive electrode materials.
[0031] In some embodiments of the present invention, the weight ratio of the above-mentioned precursor to lithium hydroxide monohydrate is 2-2.5:1, and the added amount of the M-containing compound is 0.5-2 wt % of the mixture of the precursor and lithium hydroxide monohydrate.
[0032] In some embodiments of the present invention, the precursor, lithium hydroxide monohydrate and the M-containing compound are mixed by dry mixing.
[0033] Dry mixing can prevent the doping elements in the additives from being dispersed into the wastewater, thereby reducing the cost of wastewater treatment.
[0034] In some embodiments of the present invention, M in the M-containing compound includes at least one of Na, K, Mg, B, Al and Yb.
[0035] In some embodiments of the present invention, the above-mentioned M-containing compound includes Yb 2 O 3 , YbF 3 、Yb(OH) 3 and / or Yb 2 (CO3) 3 .
[0036] In some embodiments of the present invention, the precursor is a nickel-cobalt-manganese hydroxide precursor.
[0037] In some embodiments of the present invention, the nickel-cobalt-manganese hydroxide precursor is prepared by the following method:
[0038] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution;
[0039] The salt solution, the precipitant solution and the complexing agent are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
[0040] Preferably, the NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 The molar ratio of O is (0.9-0.95):(0.01-0.05):(0.03-0.08). More preferably, it is 0.92:0.03:0.05, so that the hydroxide precursor obtained is Ni 0.92 Co 0.03 Mn 0.05 (OH) 2 .
[0041] Preferably, the precipitant solution is sodium hydroxide solution, and the complexing agent is concentrated ammonia solution.
[0042] Preferably, the nickel-cobalt-manganese hydroxide precursor is prepared by the following method:
[0043] First, NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O were mixed in a molar ratio of (0.9-0.95): (0.01-0.05): (0.03-0.08) to obtain a 2M mixed solution, which was pumped into a 2L tank reactor; at the same time, 1M NaOH solution and 3M NH 3 ·H2O, control the pH at about 11-11.5; stir the solution evenly at 45-60°C to allow it to react fully, then wash it with deionized water several times until the pH is neutral to obtain the hydroxide precursor Ni (0.9~0.95) Co (0.01~0.05) Mn (0.03~0.08) (OH) 2 .
[0044] In some embodiments of the present invention, the high temperature sintering is performed at 700-750° C. for 10-20 hours, and after cooling, a ternary positive electrode material is obtained.
[0045] Preferably, the sintering is carried out in a tubular furnace by heating the temperature to 480-530°C at 3°C / min and keeping the temperature for 2-6h, then heating the temperature to 700-850°C at 1.5°C / min and sintering for 10-20h. After sintering, the sample is naturally cooled to room temperature, taken out, and sieved with a 400-mesh sieve to obtain a ternary positive electrode material.
[0046] Preferably, oxygen is introduced during the sintering process, and the oxygen flow rate is 0.5 to 1.5 L / min.
[0047] In a second aspect, the present invention provides a high-nickel polycrystalline ternary positive electrode material prepared by the above method, wherein the chemical formula of the high-nickel polycrystalline ternary positive electrode material is Li n Ni (1-a-b) Co a Mn b M c O 2 .
[0048] In some embodiments of the present invention, the above chemical formula Li n Ni (1-a-b) Co a Mn b M c O 2 , 1.00≤n≤1.09, 0.00<a<0.04, 0.01≤b≤0.04, 0.01≤c.
[0049] Preferably, the above chemical formula Li nNi (1-a-b) Co a Mn b M c O 2 , 1.05≤n≤1.09, 0.00<a<0.20, 0.01≤b≤0.10, 0.005≤c.
[0050] Example 1
[0051] The nickel-cobalt-manganese hydroxide precursor was prepared by the following method:
[0052] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.92:0.03:0.05;
[0053] The salt solution, sodium hydroxide solution and concentrated ammonia water are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
[0054] Example 2
[0055] The nickel-cobalt-manganese hydroxide precursor was prepared by the following method:
[0056] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.7:0.2:0.1;
[0057] The salt solution, sodium hydroxide solution and concentrated ammonia water are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
[0058] Example 3
[0059] The nickel-cobalt-manganese hydroxide precursor was prepared by the following method:
[0060] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.96:0.03:0.01;
[0061] The salt solution, sodium hydroxide solution and concentrated ammonia water are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
[0062] Example 4
[0063] Weigh the Ni prepared in Example 1 0.92 Co 0.03 Mn 0.05 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, 1 wt% ytterbium oxide of a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0064] Ni 0.92 Co 0.03 Mn 0.05 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate and ytterbium oxide are fully mixed using a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 730°C in a preheated tube furnace for 12 hours. Oxygen is passed throughout the sintering process, and the gas flow rate is controlled at about 1L / min. After naturally cooling to room temperature, the sample is taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0065] The SEM image of the high nickel ternary positive electrode material prepared in this embodiment is as follows Figure 1 shown.
[0066] Comparative Example 1
[0067] This comparative example is substantially the same as Example 4, except that ytterbium oxide is not used.
[0068] Weigh the Ni prepared in Example 1 0.92 Co 0.03 Mn 0.05 (OH) 2 500 g of hydroxide precursor and 225 g of lithium hydroxide monohydrate;
[0069] Ni 0.92 Co 0.03 Mn 0.05 (OH) 2 The hydroxide precursor and lithium hydroxide monohydrate were fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 730°C in a preheated tube furnace for 12 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0070] The SEM image of the high nickel ternary positive electrode material prepared in this comparative example is as follows Figure 2 shown.
[0071] Comparative Example 2
[0072] This comparative example is basically the same as Example 1, except that ytterbium element is added during the precursor preparation process.
[0073] NiSO 4 6H 2 O. CoSO 4 7H 2 O and MnSO 4 ·H 2 O is mixed and dissolved in water to obtain a salt solution, wherein the molar ratio of nickel, cobalt and manganese is 0.92:0.03:0.05;
[0074] Then, 1 wt% ytterbium sulfate is added and dissolved in the salt solution to obtain a mixed salt solution;
[0075] The salt solution, the sodium hydroxide solution and the concentrated ammonia solution are reacted, filtered and washed with water until the pH value is neutral to obtain an ytterbium-doped nickel-cobalt-manganese hydroxide precursor.
[0076] This method adds an additive (ytterbium sulfate), which is dissolved in water. The ytterbium element is increased in the wastewater generated during the preparation process and during water washing, making it more difficult to treat the wastewater.
[0077] Example 5
[0078] This embodiment is basically the same as embodiment 4, except that the sintering is performed at 700° C. for 10 h and the gas flow rate is controlled at about 0.5 L / min.
[0079] Weigh the Ni prepared in Example 1 0.92 Co 0.04 Mn 0.05 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, 1 wt% ytterbium oxide of a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0080] Ni 0.92 Co 0.04 Mn 0.05 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate and ytterbium oxide are fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 700°C in a preheated tube furnace for 10 hours. Oxygen is passed throughout the sintering process, and the gas flow rate is controlled at about 0.5L / min. After naturally cooling to room temperature, the sample is taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0081] Example 6
[0082] This embodiment is basically the same as embodiment 4, except that the sintering is performed at 750° C. for 15 h and the gas flow rate is controlled at about 1.5 L / min.
[0083] Weigh the Ni prepared in Example 1 0.92 Co 0.03 Mn 0.05 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, 1 wt% ytterbium oxide of a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0084] Ni 0.92 Co 0.03 Mn 0.05 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate and ytterbium oxide are fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 750°C in a preheated tube furnace for 15 hours. Oxygen is passed throughout the sintering process, and the gas flow rate is controlled at about 1.5L / min. After naturally cooling to room temperature, the sample is taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0085] Example 7
[0086] This embodiment is basically the same as embodiment 4, except that the hydroxide precursor is Ni prepared in embodiment 2. 0.7 Co 0.2 Mn 0.1 (OH) 2 Hydroxide Precursors.
[0087] Weigh the Ni prepared in Example 2 0.7 Co 0.2 Mn 0.1 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, and 1 wt% of aluminum oxide in a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0088] Ni 0.7 Co 0.2 Mn 0.1 (OH) 2The hydroxide precursor, lithium hydroxide monohydrate, and alumina were fully mixed with a high-speed mixer, sieved, and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 830°C in a preheated tube furnace for 12 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary cathode material.
[0089] Example 8
[0090] This embodiment is basically the same as embodiment 4, except that the hydroxide precursor is Ni prepared in embodiment 3. 0.96 Co 0.03 Mn 0.01 (OH) 2 Hydroxide Precursors.
[0091] Weigh the Ni prepared in Example 3 0.96 Co 0.03 Mn 0.01 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, 1 wt% ytterbium oxide of a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0092] Ni 0.96 Co 0.03 Mn 0.01 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate, and ytterbium oxide were fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 720°C in a preheated tube furnace for 12 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary cathode material.
[0093] Example 9
[0094] Weigh the Ni prepared in Example 1 0.92 Co 0.03 Mn 0.05 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, and 0.4 wt% ytterbium oxide of a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0095] Ni 0.92 Co 0.03 Mn 0.05 (OH) 2The hydroxide precursor, lithium hydroxide monohydrate, and ytterbium oxide were fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 750°C in a preheated tube furnace for 15 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0096] Example 10
[0097] Weigh the Ni prepared in Example 3 0.96 Co 0.03 Mn 0.01 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, and 2.2 wt% of ytterbium oxide in a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0098] Ni 0.96 Co 0.03 Mn 0.01 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate, and ytterbium oxide were fully mixed with a high-speed mixer, sieved and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 730°C in a preheated tube furnace for 12 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0099] Embodiment 11
[0100] Weigh the Ni prepared in Example 2 0.7 Co 0.2 Mn 0.1 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, and 1 wt% of aluminum oxide in a mixture of hydroxide precursor and lithium hydroxide monohydrate;
[0101] Ni 0.7 Co 0.2 Mn 0.1 (OH) 2 The hydroxide precursor, lithium hydroxide monohydrate, and alumina were fully mixed with a high-speed mixer, sieved, and mixed again to obtain a uniform mixture without white spots, placed in a clean sagger, and sintered at 830°C in a preheated tube furnace for 12 hours. Oxygen was passed throughout the sintering process, and the gas flow rate was controlled at about 1L / min. After naturally cooling to room temperature, the sample was taken out and sieved with a 300-mesh sieve to obtain a double-modified high-nickel ternary cathode material.
[0102] Example 12
[0103] Weigh the Ni prepared in Example 1 0.92 Co 0.03 Mn 0.05 (OH) 2 500 g of hydroxide precursor, 225 g of lithium hydroxide monohydrate, 1 wt% of a mixture of hydroxide precursor and lithium hydroxide monohydrate containing a compound containing M (0.8 wt% of ytterbium oxide and 0.2 wt% of B 2 O 3 );
[0104] Ni 0.92 Co 0.03 Mn 0.05 (OH) 2 Hydroxide precursor, lithium hydroxide monohydrate, ytterbium oxide and B 2 O 3 Use a high-speed mixer to mix thoroughly, sieve and mix again to obtain a uniform mixture without white spots, place it in a clean sagger, and sinter it at 730℃ in a preheated tube furnace for 12 hours. Oxygen is passed throughout the sintering process, and the gas flow rate is controlled at about 1L / min. After naturally cooling to room temperature, take out the sample and sieve it with a 300-mesh sieve to obtain a double-modified high-nickel ternary positive electrode material.
[0105] Experimental example
[0106] The positive electrode materials of Examples 4-12 and Comparative Example 1 were assembled into button-type CR2032 batteries and subjected to cycle testing.
[0107] The specific process of button battery preparation is: weigh the modified high nickel ternary material, Super P and polyvinylidene fluoride in a mass ratio of 95:3:2, mix evenly, add an appropriate amount of NMP and stir for 3 hours to obtain a viscous slurry, use a coater to evenly coat it on aluminum foil, bake it in a vacuum oven at 120°C for 8 hours, use a roller press to press the sheet, and finally cut the pole piece with a diameter of 12mm. A pure lithium sheet with a diameter of 16mm is used as the negative electrode sheet, a 1mol / L LiPF6+DEC / EC (volume ratio 1:1) mixed solution is used as the electrolyte, and an 18mm poly Celgard propylene microporous membrane is used as the diaphragm. It is assembled into a button CR2032 battery in an argon-filled glove box. The prepared button battery uses the Xinwei test channel to perform charge and discharge tests at a voltage of 3.0~4.3V, 0.1C, 0.33C and 1C rates, and finally cycles 50 times at a rate of 1C.
[0108] The results are shown in Table 1.
[0109] Table 1
[0110] 0.1C(mAh / g) 0.33C(mAh / g) 1C(mAh / g) 1C / 100 laps Example 4 225.3 214.0 204.3 91.85% Example 5 222.7 211.5 200.1 88.74% Example 6 223.5 212.1 202.3 88.91% Example 7 214 205.7 196.0 91.98% Example 8 225.4 214.2 204.5 91.91% Example 9 220.5 209.7 198.5 87.04% Example 10 217.6 208.1 197.3 91.91% Embodiment 11 213.7 205.2 195.4 88.27% Example 12 227.5 216.2 205.9 92.37% Comparative Example 1 215.1 205.7 196.0 71.98%
[0111] It can be seen from Example 4 and Comparative Example 1 in the above table. The discharge specific capacity of Example 4 at 0.1CC rate is 225.3mAh / g, the discharge specific capacity at 0.33C is 214.0mAh / g, the discharge specific capacity at 1C is 204.3mAh / g, and the capacity retention rate of 50 cycles at 1C is 91.85%; the discharge specific capacity of Comparative Example 1 at 0.1C is 215.1mAh / g, the discharge specific capacity at 0.33C is 205.7mAh / g, the discharge specific capacity at 1C is 196.0mAh / g, and the capacity retention rate of 50 cycles at 1C is 71.98%. By comparing the two, it can be seen that the use of M-containing compounds can significantly improve its discharge specific capacity and capacity retention rate. In combination with Figure 1 and Figure 2 It can be seen that after modification, the primary particles are relatively small and more regular, and a layer of fast ion conductor will be generated on the surface, which will improve the capacity and rate performance of the ternary positive electrode material.
[0112] By observing Example 4 and Examples 9 to 12 in the above table, it can be seen that the capacity and rate performance of the ternary positive electrode material are better when the M compound is preferably contained between 0.5 and 2.0%. When the addition amount is too small, it cannot play a good role, and when the addition amount is too large, it will lead to too much inactive material in the positive electrode material.
[0113] From the above table, it can be seen that when the ytterbium compound is an M-containing compound, the cycle performance of the ternary positive electrode material is greatly improved compared with other additives. In addition to being trivalent, the ytterbium ion can also be divalent. 2 O 3 The divalent ytterbium ions can make the Ni generated by the ternary cathode material during charging 4+ Reduction to Ni 3+ , divalent ytterbium is oxidized to trivalent ytterbium, inhibiting Ni 4+ The generation of Ni 4+ It produces side reactions with the electrolyte, reducing the consumption of electrode active materials and electrolyte, and improving the material's cycle performance.
[0114] It can be seen from the above table that the addition of some additives with lower melting points to the M-containing compound has better capacity, rate and cycle performance. This is because the M-containing compound with lower melting points can more easily enter the interior of the ternary positive electrode material during the sintering process. 2 O 3 The melting point of (ytterbium oxide) is 2411°C, B 2 O 3 Melting point 450℃, B 2 O 3 During the sintering process, it has become a liquid phase and is easier to enter the interior of the material.
[0115] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for preparing a high-nickel polycrystalline ternary positive electrode material, characterized in that: The steps include: The precursor, lithium hydroxide monohydrate and the M-containing compound are mixed, sintered at high temperature, kept warm and then cooled to obtain a high-nickel polycrystalline ternary positive electrode material. Wherein, the M-containing compound includes a multivalent ionic compound whose maximum valence state is positive trivalent.
2. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 1, characterized in that: The weight ratio of the precursor to lithium hydroxide monohydrate is 2-2.5:1, and the added amount of the M-containing compound is 0.5-2 wt % of the mixture of the precursor and lithium hydroxide monohydrate.
3. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 1, characterized in that: The precursor, lithium hydroxide monohydrate and the M-containing compound are mixed by dry mixing.
4. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 1, characterized in that: The M in the M-containing compound includes at least one of Na, K, Mg, B, Al and Yb.
5. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 4, characterized in that: The M-containing compound includes Yb2O3, YbF3, Yb(OH)3 and / or Yb2(CO3)3.
6. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 1, characterized in that: The precursor is a nickel-cobalt-manganese hydroxide precursor.
7. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 6, characterized in that: The nickel-cobalt-manganese hydroxide precursor is prepared by the following method: NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O are mixed and dissolved in water to obtain a salt solution; The salt solution, the precipitant solution and the complexing agent are reacted, filtered and washed with water until the pH value is neutral to obtain a nickel-cobalt-manganese hydroxide precursor.
8. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 1, characterized in that: The high temperature sintering is carried out at 700-750° C. for 10-20 hours, and after cooling, a ternary positive electrode material is obtained.
9. A high-nickel polycrystalline ternary positive electrode material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The chemical formula of the high nickel polycrystalline ternary positive electrode material is Li n Ni (1-a-b) Co a Mn b M c O2.
10. The method for preparing a high-nickel polycrystalline ternary positive electrode material according to claim 9, characterized in that: Chemical formulaLi n Ni (1-a-b) Co a Mn b M c In O2, 1.00≤n≤1.09, 0.00<a<0.20, 0.01≤b≤0.10, 0.005≤c.
Citation Information
Patent Citations
Magnesium ion-doped graded nickel cobalt manganese oxide cathode material and its preparation method
CN109686938B